PERAN KEPUASAN KERJA DALAM MEMEDIASI PENGARUH RANSFORMATIONAL LEADERSHIP TERHADAP KOMITMEN ORGANISASIONAL KARYAWAN KSU MITRA SEJAHTERA - Pratama, I Gusti Ngurah Adhi; Supartha, Wayan Gede (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.07.TAHUN.2024DO - 10.24843/EEB.2024.v13.i07.p06, 2024)
This study aims to determine the effect of transformational leadership on organizational commitment through mediation of job satisfaction in KSU Mitra Sejahtera employees. The population used in this study were 42 employees of KSU Mitra Sejahtera. The research sample was determined as many as 42 people with saturated sampling method. Collecting data in this study by distributing questionnaires to KSU Mitra Sejahtera employees and analyzed using arithmetic average descriptive statistics, classical assumption test, path analysis, and sobel test. The results of the data analysis stated that transformational leadership had a positive and significant effect on organizational commitment, job satisfaction had a positive and significant effect on organizational commitment, transformational leadership had a positive and significant effect on job satisfaction, and job satisfaction played a partial mediation for the effect of transformational leadership on organizational commitment.